PEMIKIRAN PENDIDIKAN ISLAM MENURUT AL-FARABI - Gunaldi Ahmad (JIEBAR : Journal of Islamic Education: Basic and Applied Research, 2020)
This article will explain Al-Farabi's thoughts on Islamic education. In addition, there are several things related to Al-Farabi as well as the biography of Al-Farabi, Science, the School of Islamic Education philosophy and the educational thinking of Al-Farabi. This article is in the framework of the theory of “ilmu untuk ilmu” and where it is in the philosophy of Islamic education is an answer presented by al-Farabi through a theory of happiness. This theory of happiness as a picture of Al-Farabi's educational study of psychiatric approaches. The study used the literature research method by reading books relating to the Islamic thought figures of al-Farabi in general and particularly in his views on education. In analyzing the data, used the content analysis. This method is meant to analyse the meaning that in the thought of al-Farabi related education using inductive methods. From this paper can be found that the thought of Islamic education al-Farabi lies in the presence of goodwill that will lead to good morality, from the goodwill that brings out the theory of happiness, the meaning of the Division is science. Al-Farabi argues that the science will bring another in the way for the Sufi ways of passage is through the self-determination of various physical pleasures. The thought of al-Farabi Islamic education as a rebuttal theory of science for science. In terms of the flow of philosophy of Islamic education, al-Farabi classified into religious-rational flow.